Surgery for Moyamoya Disease in Children. (August 2019) - Appireddy, Ramana; Ranjan, Manish; Durafourt, Bryce A.; Riva-Cambrin, Jay; Hader, Walter J.; Adelson, P. David
Moyamoya disease is a chronic progressive cerebrovascular occlusive disease of the terminal portion of the internal carotid arteries associated with an acquired abnormal vascular network at the base of the brain, often leading to ischemic or hemorrhagic stroke. Moyamoya disease is a relatively common cause of pediatric stroke with a specific racial and well-identified clinical and imaging phenotype. Moyamoya disease is more prevalent in East Asian countries compared with other geographic regions with a higher incidence of familial cases and clinically more aggressive form. Moyamoya disease is one of the few causes of stroke that is amenable to effective surgical revascularization treatment. There are various surgical options available for revascularization, including the direct, indirect, or combined bypass techniques, each with variable responses. However, due to the heterogeneity of the diseases, different clinical course, geographical variables associated with the disease, and availability of a wide variety of surgical revascularization procedures, optimal selection of a surgical candidate and the surgical technique becomes challenging, particularly in the pediatric population. This brief review presents pertinent literature of clinical options for the diagnosis and surgical treatment of moyamoya disease in children.